2001
DOI: 10.1097/00006534-200111000-00045
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Fibrin Glue in Skin Grafts and Tissue-Engineered Skin Replacements: A Review

Abstract: Fibrin glue has been widely used as an adhesive in plastic and reconstructive surgery. This article reviews the advantages and disadvantages of its use with skin grafts and tissue-engineered skin substitutes. Fibrin glue has been shown to improve the percentage of skin graft take, especially when associated with difficult grafting sites or sites associated with unavoidable movement. Evidence also suggests improved hemostasis and a protective effect resulting in reduced bacterial infection. Fibrin, associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
240
0
16

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(257 citation statements)
references
References 90 publications
1
240
0
16
Order By: Relevance
“…The use of fibrin glue as a carrier of diverse elements is not new in literature however the discovery that it would be able to keep the NGF active longer, gradually liberating it in the nerve repair was considered a great advance in microsurgery 6 .…”
Section: Many Authors Have Recently Enhanced the Results Of End-mentioning
confidence: 99%
See 2 more Smart Citations
“…The use of fibrin glue as a carrier of diverse elements is not new in literature however the discovery that it would be able to keep the NGF active longer, gradually liberating it in the nerve repair was considered a great advance in microsurgery 6 .…”
Section: Many Authors Have Recently Enhanced the Results Of End-mentioning
confidence: 99%
“…However Zeng et al 3 described a liberation peak in 18 hours which is progressively reduced until its complete extinction in 14 days. Differently Currie et al 6 referred that the fibrin glue is no longer found in the repair site 10 days after its application, limiting the NGF action for a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue welding with lasers offers many advantages and has been studied in different settings during the last decades. The purpose of this study was to analyze the feasibility of a laser-mediated fixation of collagen scaffolds in comparison to clinically established methods [21].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin hydrogels harbor a great wound healing potential. They are among the most often used native hydrogels to induce angiogenesis and wound healing per se [25,26] and have been widely used as a drug delivery system [27,28].…”
Section: Introductionmentioning
confidence: 99%